Combination of bleomycin, etoposide, and cisplatin for the treatment of advanced ovarian granulosa cell tumors. Issue 3 (1st May 2008) - Pautier, P.; Gutierrez-Bonnaire, M.; Rey, A.; Sillet-Bach, I.; Chevreau, C.; Kerbrat, P.; Morice, P.; Duvillard, P.; Lhommé, C.
Abstract : The objective is to investigate the activity and toxicity of bleomycin, etoposide, and cisplatin (BEP) regimen in ovarian granulosa cell tumors (OGCTs). Twenty consecutive patients with initial metastatic (5 patients) or recurrent (15 patients) OGCT were treated; BEP regimen: B: 30 mg intravenously or intramurally on days 1, 8, and 15; E: 100 mg/m 2 /day on days 1–5; and P: 20 mg/m 2 /day on days 1–5. Median age: 42 years (range: 17–60); median follow-up: 45 months (range: 3–112). The overall response rate is 90% (nine clinical complete response [CR], nine clinical partial response) with a median duration of 24 months (range: 4–77). A second-look laparotomy performed in 11 patients showed a pathologic CR in 7 cases and microscopic disease in 1 case. Seven patients remain free of disease (at 4–84 months); 11 patients relapsed (median: 24 months, range: 13–58), 12 patients are still alive, and 9 patients are without disease (2 patients in second CR). At 4 years, overall survival and event-free survival are respectively 58% and 30%. Toxicity is evaluable for 19 patients (48 cycles). A grade 4 neutropenia occurred in 15% of cycles (in seven patients) with a febrile neutropenia in four patients. Five patients experienced a low bleomycin pulmonary toxicity. BEP regimen appears to be an active regimen for OGCT in first-line chemotherapy.